Strengthening Digitalization of Msmes through the Ciamik Application for Alisa Khadija Diy - Tatik, Tatik; Setiani, Novi; Salsabilla, Selfira; Rahma, Indah Kartika; Febrian, Fajar (Asian Journal of Community Services, 2024)
The Khadija Muslim Women Entrepreneurs Association (ALISA) is a community of Muslim women entrepreneurs under the Indonesian Muslim Scholars Association (ICMI). This community service activity (PKM) aims to produce output through a simple accounting system called the "CIAMIK" application. This application will make it easier for ALISA Khadijah ICMI DIY members in the process of preparing financial reports, as well as providing accurate information in business development. This PKM program collaborates with the Khadija DIY Muslim Women Entrepreneurs Association (ALISA). This PKM activity is carried out through regular training and mentoring regarding the operation of accounting applications, financial report analysis, and financial management for MSMEs. Implementing this mentoring activity provides an understanding for ALISA Khadijah ICMI DIY members to be able to operate and apply the CIAMIK application to help business processes.